2014
DOI: 10.1159/000358663
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Microenvironment Changes the Secretory Profile of Mesenchymal Stem Cells to Recruit Mesenchymal Stem Cells

Abstract: Background/Aims: Human bone-marrow mesenchymal stem cells (hBMSCs) are widely transplanted into inflammatory microenvironment to accelerate tissue regeneration. Transplanted hBMSCs recruit host hBMSCs through a poorly understood mechanism. This study was aimed to determine whether and how inflammatory microenvironment influenced the host-hBMSCs-recruiting capability of transplanted hBMSCs. Methods: Pro-inflammatory factors, including IL-1β, IL-6 and TNF-α, were utilized to mimic inflammatory microenvironment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…In this context, implanted MSCs modulate the local microenvironment to stimulate the host's innate regenerative activity via paracrine actions (11). This notion is further reinforced by our finding that the inflammatory microenvironment leads to a massive amplification of the paracrine capacity of MSCs (12). The release of CXC chemokine family members, such as growth-related oncogenes C-X-C motif ligand (CXCL)1, CXCL2, CXCL3, CXCL5, CXCL6, CXCL7, and CXCL8, is significantly enhanced after inflammatory stimulation.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…In this context, implanted MSCs modulate the local microenvironment to stimulate the host's innate regenerative activity via paracrine actions (11). This notion is further reinforced by our finding that the inflammatory microenvironment leads to a massive amplification of the paracrine capacity of MSCs (12). The release of CXC chemokine family members, such as growth-related oncogenes C-X-C motif ligand (CXCL)1, CXCL2, CXCL3, CXCL5, CXCL6, CXCL7, and CXCL8, is significantly enhanced after inflammatory stimulation.…”
mentioning
confidence: 71%
“…We recently reported that implanted donor MSCs could induce the homing of host EPCs to the bone defect site, an initiating event of vasculogenesis (4). Moreover, the release of CXCR2 ligands from MSCs is significantly enhanced in an inflammatory microenvironment (12). Therefore, a major goal for us is to determine the impact of CXCR2-mediated signaling during bone repair induced by TECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This helper profile has been observed in neural stem cells and mesenchymal stem cells. In the case of mesenchymal stem cells, this function can play an important role in changing the macrophage proinflammatory profile into a proregenerating role, once there is no longer an urgent need for a robust immune response [14][15][16] . Understanding the biology of stem cells and their niches, as well as the mechanisms involved in their multipotent state, are basic criteria to achieve great experimental results and to take the next step towards clinical trials.…”
Section: Adult Stem Cellsmentioning
confidence: 99%
“…Assim como outros tipos de células-tronco, as CTAs são capazes de promover regeneração tecidual por diversos mecanismos. Além de promover repovoamento do tipo celular perdido (seja se diferenciando diretamente nele, ou atraindo CTs no entorno para fazer isso), elas também apresentam potencial imuno-modulador: alguns estudos já comprovaram que elas são capazes de inibir o processo inflamatório local secundário a uma lesão, e estimular a regeneração tecidual 57 . CT mesenquimais, por exemplo, são capazes de mudar o fenótipo dos macrófagos ao serem transplantadas para um tecido lesado, inibindo sua atividade pró-inflamatória e estimulando sua atividade pró-regenerativa 57,58 .…”
Section: Uma Nova Alternativa: Células-tronco Endógenasunclassified